2003
DOI: 10.1097/00004770-200312000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome in Endodontics: The Toronto Study. Phase 1: Initial Treatment

Abstract: This study assessed the 4- to 6-yr outcome of initial endodontic treatment during Phase 1 of the "Toronto Study" project. A total of 450 teeth were treated, alternating the "Schilder" technique and step-back with lateral condensation, and examined clinically and radiographically by an independent examiner. Apical periodontitis was recorded as absent (periapical index < 3) or present (periapical index > or = 3) and outcome dichotomized as "healed" (no apical periodontitis, no signs or symptoms) or "disease." Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
248
4
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(299 citation statements)
references
References 15 publications
28
248
4
19
Order By: Relevance
“…These results are in agreement with earlier findings that teeth with apical periodontitis have a significantly lower success rate than those without such lesions. [5][6][7][8][9][10] Stepwise logistic regression analysis revealed that preoperative apical radiolucency was important for predicting treatment failure, with an OR of 3.6 (p = 0.011): in other words, teeth with diseased periapical status have a 3.6 times greater risk of failure than those with a normal periapex. This OR is similar to the values reported in the Toronto studies, 8,9 but lower than that found in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are in agreement with earlier findings that teeth with apical periodontitis have a significantly lower success rate than those without such lesions. [5][6][7][8][9][10] Stepwise logistic regression analysis revealed that preoperative apical radiolucency was important for predicting treatment failure, with an OR of 3.6 (p = 0.011): in other words, teeth with diseased periapical status have a 3.6 times greater risk of failure than those with a normal periapex. This OR is similar to the values reported in the Toronto studies, 8,9 but lower than that found in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Stepwise logistic regression analysis revealed that preoperative apical radiolucency was important for predicting treatment failure, with an OR of 3.6 (p = 0.011): in other words, teeth with diseased periapical status have a 3.6 times greater risk of failure than those with a normal periapex. This OR is similar to the values reported in the Toronto studies, 8,9 but lower than that found in other studies. 7,10,21 In addition to apical radiolucency, preoperative gingival swelling and sinus tract of pulpal origin had a significant effect on the nonsurgical endodontic treatment; the least favorable healed rate (51.6%) was associated with this factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success rate of root canal treatment has been based on radiographic healing or whether an endodontically treated tooth remains present and functioning in the oral cavity [1]. According to Imura et al [2], of 1376 teeth treated in an initial endodontic treatment sample, the success rate was 94%.…”
Section: Introductionmentioning
confidence: 99%